PENERAPAN SISTEM PERTANIAN ORGANIK DI KELOMPOK TANI MEKAR TANI JAYA DESA CIBODAS KABUPATEN BANDUNG BARAT - Fauzia Imani; Anne Charina; Tuti Karyani; Gema Wibawa Mukti (Mimbar Agribisnis: Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2018)
The application of conventional farming systems causes negative impacts for the environment and consumers, an effort made to deal with the negative impact is by changing conventional farming systems into organic. In 2010, the government released the Go Organic program and the area of certified organic farming reached into maximum point in that year. Until now there are many farmers who claim that their agricultural products are the organic one. Mekar Tani Jaya Farmer Group has conducted organic cultivation for 18 years. The aim of this research is to find out  the application of organic farming system in Mekar Tani Jaya in accordance with SNI 6729: 2016, and also to know what are the obstacles faced by Mekar Tani Jaya in the implementation of organic farming system. This research is used qualitative descriptive method with through a case study technique. This research also using Miles and Huberman data analysis model and  fishbone analysis model. The results is the percentage of conformity organic farming system by Mekar Tani Jaya Farmer Group with SNI 6729 : 2016 is about 94 percent (%). Meanwhile, the main problem that faced by Mekar Tani Jaya  Farmer Group is not all of the organic farming system according to SNI 6729: 2016 can be applied thus make an impact to other aspects.Keywords: Organic Farming, SNI 6729 : 2016, farmer group.